Peculiarities of the application of the knowledge of mathematics in real-life situations and solving problems in case of senior form students having moderate special needs - Tomėnienė, Laima (Social Welfare: Interdisciplinary Approach, 2011)
The article deals with the peculiarities of the application of the knowledge of mathematics in real life situations of students with moderate special needs who study in senior forms of mainstream schools. The research data have been collected applying quantitative approach. By the method of questionnaire survey it has been investigated how students with moderate special educational needs who study in 8-10 forms of mainstream school are able to apply possessed knowledge of mathematics in real-life situations and solving problems of practical character, the peculiarities of their functional mathematical literacy have been assessed. The results of the research have shown that the level of functional mathematical literacy of the majority of students with moderate special educational needs who have participated in the pilot research is not sufficient, the knowledge of mathematics is not strong, students lack practical abilities and perception how and where possessed knowledge could be applied in everyday activity.
Keywords: students having moderate special educational needs; practical application of mathematical knowledge; abilities; mathematical literacy; problem solving